Mucosal-associated invariant T cells repress group 2 innate lymphoid cells in Alternaria alternata-induced model of allergic airway inflammation - Shimizu, Yasuo; Horigane-Konakai, Yukiko; Ishii, Yoshii; Sugimoto, Chie; Wakao, Hiroshi (Frontiers in Immunology, 2022)
Mucosal-associated invariant T (MAIT) cells, a blossoming member of the innate-like T cells, play a pivotal role in host defense through engaging the mucosal immunity. Although it has been suggested that MAIT cells are somehow implicated in the allergic airway inflammation mediated by group 2 innate lymphoid cells (ILC2s) such as asthma, the precise role(s) of MAIT cells in such inflammation has remained elusive. To explore the possible roles of MAIT cells in the inflammation, we examined whether MAIT cells suppressed the production of T helper (Th) 2 and inflammatory cytokines from ILC2s, and constrained the proliferation of ILC2s, both of which are prerequisite for airway inflammation. Given that laboratory mice are poor at MAIT cells, a novel mouse line rich in MAIT cells was used. We found that mice rich in MAIT cells showed alleviated airway inflammation as evidenced by reduced infiltration of the immune cells and hyperplasia in goblet cells in the lung concomitant with compromised production of Th2 and inflammatory cytokines, while wild type mice exhibited severe inflammation upon challenge with the fungal extracts. In vitro coculture experiments using purified ILC2s and MAIT cells unrevealed that cytokine-stimulated MAIT cells suppressed ILC2s to produce the cytokines as well as to proliferate most likely via production of IFN-γ. Furthermore, reconstitution of the allergic airway inflammation in the highly immunocompromised mice showed that ILC2-mediated inflammation was alleviated in mice that received MAIT cells along with ILC2s. We concluded that MAIT cells played a crucial role in suppressing the cytokine-producing capacity of ILC2s and ILC2 proliferation, that ultimately led to decrease in the allergic airway inflammation. The results open up a novel therapeutic horizon in ILC2-mediated inflammatory diseases by modulating MAIT cell activity.